2019
DOI: 10.1016/j.celrep.2018.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Liver-Specific AMPK Activation Protects against Diet-Induced Obesity and NAFLD

Abstract: SUMMARY The AMP-activated protein kinase (AMPK) is a highly conserved master regulator of metabolism, whose activation has been proposed to be therapeutically beneficial for the treatment of several metabolic diseases, including nonalcoholic fatty liver disease (NAFLD). NAFLD, characterized by excessive accumulation of hepatic lipids, is the most common chronic liver disease and a major risk factor for development of nonalcoholic steatohepatitis, type 2 diabetes, and other metabolic conditions. To assess the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
174
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(191 citation statements)
references
References 49 publications
11
174
2
4
Order By: Relevance
“…This may be one of the mechanisms by which hepatic deletion of ANGPTL4 improves metabolic function following HFD-induced obesity. This hypothesis is supported by the recent studies on the overexpression of AMPK in the mouse liver (46,47). Data from these studies indicate that activation of AMPK in the liver decreases lipid deposition not only in the liver, but also in the AT.…”
Section: Discussionmentioning
confidence: 55%
“…This may be one of the mechanisms by which hepatic deletion of ANGPTL4 improves metabolic function following HFD-induced obesity. This hypothesis is supported by the recent studies on the overexpression of AMPK in the mouse liver (46,47). Data from these studies indicate that activation of AMPK in the liver decreases lipid deposition not only in the liver, but also in the AT.…”
Section: Discussionmentioning
confidence: 55%
“…Genetic (10)(11)(12)(13) and pharmacological (7) activation of AMPK in liver improves hepatic steatosis. This led to the hypothesis that AMPK activation could be useful for the treatment of early stages of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…(6,8) We confirmed these data and thereby validated our genetic models by the demonstration that the loss of AMPK in skeletal muscle, but not in liver, attenuated the beneficial effect of the compound on glucose tolerance. Genetic models have provided contradictory results concerning whether the stimulation of AMPK affects whole-body fat oxidation, (11)(12)(13) and pharmacological studies with selective activators have not yet been carried out. As shown here, AMPK activation by compound 1 lowered the RQ and stimulated fat oxidation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeting hepatic AMPK with an AMPK-specific small-molecule activator reduces liver steatosis and improves glucose disposal in obese mice 26,27 . Recently, Garcia et al 28 showed that liver-specific AMPK activation in DIO mice protects against liver steatosis.…”
Section: Discussionmentioning
confidence: 99%